PENGARUH BUDAYA ORGANISASI TERHADAP MOTIVASI KERJA KARYAWAN BAGIAN PRODUKSI DI SEBUAH PERUSAHAAN X - Dhevyanggi Sendy Naibaho; Sutarto Wijono (Direktorat Riset dan Pengabdian Masyarakat Universitas Bina Darma Palembang, 2022)
Each company has its policy in determining a work rule. The policy is based on an organizational culture that is implemented within the company. In this study, company X has an organizational structure that changes ownership, thus making the culture applied also changes. Employees within the scope of the company lack an understanding of the culture that is use and this greatly affects the production results of company X. The purpose of this study is to see the influence of organizational culture on the work motivation of employees of the production department at company X, using quantitative research methods. The results of hypothesis testing using the F test (ANOVA) obtained an F count of 49.760 (49.760 > 4.038393), and the Sig value obtained was 0.000 (< a = 0.05). In addition, the results of the coefficient of determination test obtained an Adjusted R Square value of 0.494. Thus, the result of this study is the influence of organizational culture on the work motivation of 49.4%.